2013
DOI: 10.1177/1057083713494012
|View full text |Cite
|
Sign up to set email alerts
|

Together Through Transitions

Abstract: In the field of music teacher preparation, the transition from teacher to teacher educator can be a time of uncertainty and anxiety. Knowing the potential for struggle during formation of a teacher educator identity, we investigated our personal development as music educators at two points: (a) preparing to enter academia and (b) mentoring a future teacher educator. The purpose of this narrative inquiry study was to document the emergent identity of Vanessa, a graduate student transitioning to music teacher ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 22 publications
0
24
1
Order By: Relevance
“…Given concerns expressed by the participants and authors of the music education literature described, we were interested in examining IP with respect to the primary responsibilities of music education faculty positions (Bond & Koops, 2014; Conway et al, 2016; Martin, 2016; Pellegrino et al, 2014). We were interested in whether IP could explain some of the feelings of anxiety about teaching and research that participants in those studies expressed or provide an explanation for why some music education faculty do not continue to undertake and publish research after completing the doctorate (Sims, 2016; Sims & Cassidy, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given concerns expressed by the participants and authors of the music education literature described, we were interested in examining IP with respect to the primary responsibilities of music education faculty positions (Bond & Koops, 2014; Conway et al, 2016; Martin, 2016; Pellegrino et al, 2014). We were interested in whether IP could explain some of the feelings of anxiety about teaching and research that participants in those studies expressed or provide an explanation for why some music education faculty do not continue to undertake and publish research after completing the doctorate (Sims, 2016; Sims & Cassidy, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Given the complexity of the job of music teacher educator, the transition from doctoral student to music education faculty member is likely to present a variety of challenges and may even be considered a struggle for some (Martin, 2016). A growing body of literature in music education has begun to address related issues, including the development of identity (Bond & Koops, 2014; Conway, Eros, Pellegrino, & West, 2010), socialization into teaching (Conkling & Henry, 2008), learning to teach graduate students (Conway et al, 2016), peer mentoring (Draves & Koops, 2011), and the role of a professional development community (Pellegrino et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, results from this study may reflect selection bias. Though researchers have suggested music education doctoral students may struggle to adopt the identity of "music teacher educator" (Bond & Koops, 2014;Conway et al, 2010;Pellegrino et al, 2014), results from this study showed that music education doctoral students identified more strongly with the identities of "music teacher educator" and "teacher mentor" than identities such as "student" or "K-12 music teacher." This association could be attributed to the fact that the majority of participants were relatively far into their programs, averaging around 44 hours completed toward the doctoral degree.…”
Section: Discussion and Recommendations For Future Researchmentioning
confidence: 58%
“…In this sense, Jorgensen (2009) has shown particular interest on narrative inquiry in music education; and Jones & Parkes (2010) analyzed the reasons for the choice of career in music education related to the construction of student's identity. Bond & Huisman Koops (2014) studied the identity of a beginner teacher of music through narrative inquiry. Kallio (2015), with her "Factional stories", has opened a new and interesting methodological line.…”
Section: Methods and Backgroundmentioning
confidence: 99%